(untitled) (Biological Sciences - PJSIR, 1999)
Polianthes tube rosa Linn., belongs to the family Liliaceae and is native of America though cultivated inFar East Indo-China. The scales of bulbs are reported to be antiposmadic. These bulbs are also used to treat malaria a decoction of this plant is a remedy for Gonohorrea and is used as mutarative polutice (Perry 1980). In view of pharmacological significance of Polianthes tuberosa, we carried out phytochemical investiga- tion on butanolic extract of the bulbs of this plant.